Pengembangan Industri Tas Kulit Berbasis Kearifan Lokal di Desa Nambangrejo Kecamatan Sukorejo Kabupaten Ponorogo - Rohmat, Rohmat; Fikriawan, Suad (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The craft industry in Indonesia, including leather bag production, plays a crucial role in local economic development and cultural preservation. Nambangrejo Village in Sukorejo District is one example of a leather bag craft center that has grown and developed over generations. The tradition of leather bag making in this village began with the skill of creating simple leather goods for daily needs, and over time evolved into more complex and economically valuable leather bag production. This study aims to explore the potential, challenges, and development strategies of the leather bag industry based on local wisdom in Nambangrejo Village. Using a qualitative approach through in-depth interviews and field observations, this research found that the leather bag industry in this village faces challenges such as globalization, market competition, and changing consumer preferences. Although production is still limited to a small scale, its development potential is significant if supported by appropriate strategies, such as training, network collaboration, and product innovation. Additionally, there are three key roles that can support the development of local wisdom in the leather bag industry: the roles of the government, academics, and the craftsmen themselves. With a comprehensive approach, this industry has the potential to become a strong local economic force that can compete in a broader market while maintaining its cultural idenity.